The Students’ Communicative Readiness for Their Professional Activity as Teachers of English - Ivanashko, Oksana; Vichalkovska, Nataliya (East European Journal of Psycholinguistics, 2014)
The influence of psychological factors on the pedagogical communication style of future teacher is examined. Under the pedagogical communication style we mean individual and typological peculiarities of social and psychological interaction of teacher and pupils. It depends on personal characteristics of the teacher and communication situation parameters. Pedagogical activity style is accompanied by behavior styles. Each style suggests the dominance of monological or dialogical forms of communication. The interrelation of future professional activity specificity and communication function development, availability level of organizational skills is analyzed. The study of learning style characteristics of communication. The study of pecularities of educational communication style is carried out. Properly used individual style of pedagogical communication assists in solving the whole complex of tasks:  pedagogical effect becomes adequate for teacher’s personality, communication process with audience becomes pleasant, procedure of establishing interrelations with pupils is essentially facilitated, increases efficiency of information transfer. Made conclusions indicate the need to create conditions for the providing of controlled entring of graduates into the pedagogical profession.ReferencesKan-Kalik, V. A. (1979) Osnovy professionalno-pedagogicheskogo obshchenia [Fundamentals ofprofessional and pedagogical communication]. Groznyi: Checheno-Ingushetia Publishers.Shcherban, T. D. (2004). Psykholohiya navchalnoho spilkuvannia [Psychology of EducationalCommunication]. Kyiv: Millennium.Zabrotskyi, M. M. (2005). Do vyznachennia struktury komunikatyvnoi kompetentnosti pedahoha.[Determining the structure of communicative competence of a teacher], Naukovyi Chasopys NPU imeniM. P. Drahomanova, Series 12 «Psychological Sciences» , No 6 (30), part 1, 192.Zasiekina, L. V. (2000). Problema humanizatsii osvity ta profesiinoho myslennia [The problem ofeducation humanization and professional thinking of a teacher], Mova i kultura, 1, 68−70.
Keywords: communication preparedness; pedagogical communication style; communication forms; communicational skills; organizational skills; verbal means.